1989
DOI: 10.2136/sssaj1989.03615995005300020020x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Electrical Conductivity and Soil Salinity: New Formulations and Calibrations

Abstract: A new model describing the relation between bulk soil electrical conductivity (ECa), volumetric content (θw) and electrical conductivity of soil water (ECw) is given along with supporting evidence for its validity. The new model distinguishes between the water and salt present in the soil in the “immobile” (fine pores) and “mobile” (large pores) phases. It provides a possible physical meaning to the transmission coefficient (T) previously used in an earlier model and eliminates a limitation of that model which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
346
1
31

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 492 publications
(409 citation statements)
references
References 0 publications
12
346
1
31
Order By: Relevance
“…This high correlation is expected because it reflects the influence of salts on the EC a reading and because these properties are highly correlated (Kaffka et al, 2005). Salts and Na + concentrations increased soil solution conductivity (Rhoades et al, 1989) and is consistent with findings in previous studies (Kaffka et al, 2005).…”
Section: Relationships Among Ec a With Soil Properties And Nutrient Csupporting
confidence: 90%
See 3 more Smart Citations
“…This high correlation is expected because it reflects the influence of salts on the EC a reading and because these properties are highly correlated (Kaffka et al, 2005). Salts and Na + concentrations increased soil solution conductivity (Rhoades et al, 1989) and is consistent with findings in previous studies (Kaffka et al, 2005).…”
Section: Relationships Among Ec a With Soil Properties And Nutrient Csupporting
confidence: 90%
“…These series had higher salt content values (higher EC 1:2.5 ) and clay content than the Canals series. In the model proposed by Rhoades et al (1989), they identified that the major factors that influence EC a are: (I) the electrical conductivity of the soil solution associated with continuous and discontinuous pores; (II) the volumetric content of soil particles; (III) the electrical conductivity of the soil particles and; (IV) the volumetric water content in the soil. The first, second and third factor are influenced and increased by soil salinity (Malicki and Walczak, 1999), clay content (Rhoades and Corwin, 1990), and CEC (Shainberg et al, 1980), respectively.…”
Section: Exploratory Analysis Of Ec a Soil Properties And Nutrient mentioning
confidence: 99%
See 2 more Smart Citations
“…All of the factors determining the leaching factor for both total-Ni-based EC50 and solution-Ni-based EC50 are related to the immediate adsorption capacity of soil and thus the leachability of Ni added as soluble salt to soil. Particularly, EC is an indicator for soil salinity (Rhoades and Corwin 1990;Rhoades et al 1989), and salinity can largely impact the retention of soluble metals added to soil through competitive adsorption and salt effect enhancing the solubility of the added salt. Therefore, in Hulunber soil with highest EC high leachability of dissolved Ni in soil solution may be responsible for the highest leaching factor.…”
Section: Leaching Effect On Ni Concentration and Ec50 In Soilsmentioning
confidence: 99%